Analisis kontribusi kepemimpinan kepala sekolah terhadap kinerja guru sekolah menengah kejuruan - Nellitawati Nellitawati; Fadila Yunistisa (Jurnal Konseling dan Pendidikan, 2022)
The purpose of this study was to analyze the contribution of principals’ leadership to the performance of vocational high school teachers. The research method used is descriptive quantitative. The research sample comprised 80 teachers from various vocational schools in the city of Padang, obtained through purposive random sampling. We collected data through two instruments, the principal’s leadership instrument and the teacher’s work perfomance scale. Each instrument uses a 5-point Likert scale with 40 items (principal leadership instrument) and 36 items (teacher performance instrument). We analyzed data with descriptive statistics and linear regression using Jeffrey’s Amazing Statistics Program (JASP). The results showed that the principal’s leadership contributed positively to the performance of SMK teachers in the city of Padang. The results indicate that there is a need to increase the intensity of the principal’s leadership in order to improve the performance of vocational school teachers in the city of Padang.